2019
DOI: 10.21273/horttech04425-19
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Fruit Quality Traits of Two Plantain Cultivars Grown at Two Locations in Puerto Rico under Black Leaf Streak Disease Pressure

Abstract: Plantain (Musa balbisiana AAB) is a tropical rhizomatous perennial plant in the genus Musa spp., closely related to banana (Musa acuminata AAA). It is an important cash crop and staple for inhabitants in many parts of the world, including various ethnic groups in the United States. Black leaf streak disease (BLSD) or black sigatoka, caused by Pseudocercospora fijiensis (formerly Myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Cultivars exhibited drastic yield differences between the mother (year 1) and ratoon (years 2, 3) crops (Tables 3 and 5). Contrary to the rapid yield decline that occurs in commercial plantain production after harvest of the mother crop (Goenaga et al, 1993(Goenaga et al, , 2019, banana yields tend to increase in successive ratoon crops after harvest of the mother crop (Goenaga and Irizarry, 1995;Irizarry et al, 1989). In this study, the bunch yield obtained by the 'FHIA-17' second ratoon crop was 37% and 8% higher in Corozal and Isabela, respectively, than the mother crop.…”
Section: Resultscontrasting
confidence: 64%
“…Cultivars exhibited drastic yield differences between the mother (year 1) and ratoon (years 2, 3) crops (Tables 3 and 5). Contrary to the rapid yield decline that occurs in commercial plantain production after harvest of the mother crop (Goenaga et al, 1993(Goenaga et al, , 2019, banana yields tend to increase in successive ratoon crops after harvest of the mother crop (Goenaga and Irizarry, 1995;Irizarry et al, 1989). In this study, the bunch yield obtained by the 'FHIA-17' second ratoon crop was 37% and 8% higher in Corozal and Isabela, respectively, than the mother crop.…”
Section: Resultscontrasting
confidence: 64%
“…There were also pronounced differences in pseudostem girth among plantain hybrids and the local variety Ebang. Larger pseudostem girth can help in sustaining yields over several production cycles (Goenaga et al, 2019). In this study, there was a significant correlation (r = 0.44) between plant girth and bunch yield.…”
Section: Discussionmentioning
confidence: 49%
“…Plantains are starchy bananas that constitute over 80% of world banana (Musa spp.) production and are considered one of the major staple food and economic crop for about 70 million people in West and Central Africa (Goenaga et al, 2019). Worldwide, green or ripe fruits are consumed in several forms including fried, baked, roasted, pounded as fufu, porridge, and flour, and are eaten alone or together with other foods depending on local cuisines (Etebu & Young-Harry, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Plantain is susceptible to deficiencies in soil water, with expanding tissues such as emerging leaves and increase in fruit size are usually among the most likely to be affected [16]. The number of leaves present during floweringfruiting is a critical physiological feature for effective fruit-filling considering the fact that no new leaves are produced after this stage [46]. [22] reported that French plantain on polluted soil had broader leaves than plants on unpolluted soil.…”
Section: Weeks After Plantingmentioning
confidence: 99%